Profile of Ectopic Pregnancy Cases in a Tertiary Hospital - Singh, Jitendra Kumar; Dangal, Ganesh (Journal of Nepal Health Research Council, 2021)
Background: An ectopic or extra uterine pregnancy is one in which the blastocyst implants anywhere other than the endometrial lining of the uterine cavity. The objective of the study was to find incidence, risk factors, clinical presentation and mode of management of ectopic pregnancy.Methods: Observational study was conducted at Paropakar Maternity and Women’s Hospital, Thapathali, Kathmandu. All the relevant data were recorded in performa. The collected data were entered in MS Excel and exported into SPSS 26 version for statistical analysis.Results: About one third of the patients 10 (33.3%) was of 25-29 age group.The most common risk factor was pelvic infection in 23 (76.6%) cases, abortion in 11 (36.7%), and abdominal surgery in 8 (26.7%) of cases. The of classic triad of amenorrhea (100%), pain abdomen (99.7%) and per vaginal bleeding (66.7%). Ruptured ectopic seen in 26 (86.7%) cases, unruptured status in 1 (3.3%) case, tubal abortion in 1(3.3%) case and organized ectopic in 2(6.7%) cases. The most common site was found to be ampulla in 23 (76.7%) cases, fmbria 3(10%) cases, corneal in 3(10%) cases and ithmus in 1 (3.3%) case. All the cases managed surgically, of them unilateral salphingectomy, unilateral salphingo-opherectomy and wedge resection for corneal pregnancy were done in 25(83.3%), 2(6.7%) and 3(10%) cases respectively.Conclusions: Ectopic pregnancy mostly present as ruptured form in young females in our context. Pelvic infection is the commonest risk factor with ampulla being the commonest site. All cases required surgical intervention in form of unilateral salphingo-opherectomy and wedge resection.Keywords: hCG ; ectopic pregnancy; salphingectomy; ultrasonography; UPT